The Correlation Between Emotional Maturity and Problem-Solving Ability in Yogyakarta Students - Muadz, Rafif Nugraha; Rohmadani, Zahro Varisna; Khan, Zeeshan (The Indonesian Institute of Science and Technology Research, 2024)
Students are people who attend school, and from the perspective of society, students are the vanguard of the modern era. However, being a student also comes with several challenges and tasks that occasionally conflict with those encountered outside the academic area. These challenges frequently cause problems. The need for decision-making abilities or the appropriate action to solve the issue will follow. The study aims to identify the correlation between emotional maturity and problem-solving among students in Yogyakarta. This study employed a quantitative research method with a correlational approach and used two variable scales. The data analysis used Pearson Correlation Product Moment. The results showed that emotional maturity and problem-solving among students in Yogyakarta correlated with a significant value of 0.003 and a Pearson correlation of 0.085, so it can be concluded that these two variables correlated. Students are expected to be able to control their emotions and solve problems more effectively to make life simpler for themselves and others.